2011
DOI: 10.1364/oe.19.011804
|View full text |Cite
|
Sign up to set email alerts
|

40 Gb/s silicon photonics modulator for TE and TM polarisations

Abstract: A key device in future high speed short reach interconnect technology will be the optical modulator. These devices, in silicon, have experienced dramatic improvements over the last 6 years and the modulation bandwidth has increased from a few tens of MHz to over 30 GHz. However, the demands of optical interconnects are significant. Here we describe an approach based on a self-aligned wrap around p-n junction structure embedded in a silicon waveguide that can produce high-speed optical phase modulation, whilst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(68 citation statements)
references
References 17 publications
1
66
0
Order By: Relevance
“…Firstly, the waveguide should support only single mode propagation to avoid performance degradation in interferometric and resonant structures. Secondly, if polarisation independence is required without a polarisation diversity scheme, the dimensions should be chosen to support both fundamental TE and TM modes and the effective index and optical loss for both modes should be the same [38]. The waveguide geometry also affects the confinement of the optical mode within the waveguide and therefore the degree of interaction with the region of changing refractive index (depletion region).…”
Section: Chirpmentioning
confidence: 99%
See 4 more Smart Citations
“…Firstly, the waveguide should support only single mode propagation to avoid performance degradation in interferometric and resonant structures. Secondly, if polarisation independence is required without a polarisation diversity scheme, the dimensions should be chosen to support both fundamental TE and TM modes and the effective index and optical loss for both modes should be the same [38]. The waveguide geometry also affects the confinement of the optical mode within the waveguide and therefore the degree of interaction with the region of changing refractive index (depletion region).…”
Section: Chirpmentioning
confidence: 99%
“…To overcome this issue and to therefore create a design which is robust to fabrication variations and therefore results in a high yield, a fabrication process using selfaligned pn junction formation has been devised [37,38]. The process used by Thomson et al is shown in Figure 6.…”
Section: Chirpmentioning
confidence: 99%
See 3 more Smart Citations